From a sick mind to a cultural soul: knowledge, legal and indigenous forms in Colombia (2009)
With the consecration in the decade of 1990 of a special regime for the indigenous towns, an as old problem arises as complicated: the definition of the native like legal subject. Analyzing the relations between social practices, to knowledge and legal fo